Introduction to cellulose-based nanobiosorbents - Mussagy, Cassamo Ussemane [UNESP]; Magri, Agnes (Elsevier, 2022)
Currently, the common absorbent materials available in the market are derived from non-renewable petrochemicals sources which exhibit poor environmental biocompatibility. This lack of sustainability has driven research towards developing more biocompatible and eco-friendly alternatives natural bio-based materials for wastewater treatment, environmental remediation, food processing, medicine, nanosensors among others with low cost, and with no harmful by-products generation. As shown in this book, nanomaterials, as absorbents, offer several advantages over the conventional; due to the low-cost, high absorption capacities, less sludge regeneration and the availability of these compounds in the world. Among these, lignocellulosic biomass have attracted the attention of several industries due to the promising applications as absorbent. The main component of lignocellulosic material, namely: cellulose (natural polymer), has been applied directly as bio-sorbent in its natural form obtained from agri-food wastes (cassava bagasse, rice straw banana peel, corncob, among others).
Keywords: Bacterial cellulose; Cellulose nanocrystals; Cellulose nanofibers; Direct modification; Environmental remediation; Graft copolymerization; Lignocellulosic material; Nanosensors; Wastewater treatment